Dynamics of perifocal reactions to the application of antimicrobial gel in one-stage hip replacement under conditions of staphylococcal infection in the experiment - S. A. Bozhkova; Yu. S. Korneva; V. N. Liventsov; O. S. Legonkova; L. O. Anisimova; G. I. Netylko; M. Sh. Gadzhimagomedov; B. G. Akhmedov (Acta Biomedica Scientifica, 2024)
Background. Local antibacterial therapy in the treatment of osteomyelitis significantly increases the effectiveness of surgical debridement.The aim of the work. To assess in an in vivo experiment the dynamics of perifocal tissue reactions to the application of an original polyvinylpyrrolidone-based antimicrobial gel in a one-stage treatment of implant-associated infection in the hip joint in rabbits.Methods. Implant-associated infection was modeled by inserting Staphylococcus aureus-infected wires into the medullary canal of the femur of rabbits (n = 12). On the day 14, we removed the wire and performed radical surgical treatment of the suppurative focus and hip replacement. The animals were divided into two groups: experimental group – with application of the original antimicrobial gel at the stage of hip replacement (n = 6); comparison group – without gel application (n = 6). For morphological studies, animals were sacrificed on the days 10, 45 and 90 after hip replacement, changes in soft tissues and the bone marrow canal were assessed, and cell populations were counted with statistical data processing.Results. The application of the original antimicrobial gel causes statistically significant decrease in the number of neutrophils in the soft tissues surrounding the implant in the comparison group at all stages. Moreover, in the experimental group, at early stages the number of lymphocytes, plasmacytes and macrophages was statistically significantly higher; on the day 45, a statistically significantly larger number of lymphocytes was registered, and on the day 90 – a statistically significantly larger number of multinucleated and epithelioid cells.Conclusion. The experiment histologically confirmed the effectiveness of application of the original antimicrobial gel to stop infectious inflammation in soft tissues and the bone marrow canal during surgical debridement of an osteomyelitic lesion followed by hip replacement. A pronounced giant cell reaction aimed at removing the polyvinylpyrrolidone-based gel requires further research in terms of its outcomes.